An analysis of the effect of public policy on community garden organisations in Edinburgh. Issue 2 (1st February 2016) - Witheridge, Jennifer; Morris, Nina J.
Abstract : Several community gardens have been developed in Edinburgh over the past five years, which reflects renewed interest in "grow your own" projects, and the recognition of the associated environmental and social health benefits they provide. Community gardens have been included in a range of policy documents at national and local levels, acknowledging their contribution to sustainable food systems, health and well-being and environment and biodiversity. This research explores how public policy influences community garden practice and, reflexively, how organisations running community gardens in the third sector are represented in public policy frameworks. A mixed methodology of desk-based research of policy documents, associated reports and academic literature; and informal interviews with community gardens staff and organisers was utilised. It was found that while community gardens are represented in policy, at a national level the framing of community gardens and related food growing projects as "alternative" hinders their full potential. Community gardens fulfil a wide range of policy goals, particularly in the health, social capital and well-being sectors which can minimise their capacity to contribute to local food production in a substantial way. It is proposed that community gardens could be normalised by promoting gardens in visible locations in neighbourhoods and within local plans; and through reflexive strategic and community action utilising a reasoning backwards approach to planning and funding.